Change in p53 nuclear localization in response to extracellular matrix stiffness - Yan Zu; Jing Du; Yipu Xu; Mengying Niu; Canlin Hong; Chun Yang (Smart Medicine)
Abstract Chondrocytes are commonly applied in regenerative medicine and tissue engineering. Thus, the discovery of optimal culture conditions to obtain cells with good properties and behavior for transplantation is important. In addition to biochemical cues, physical and biomechanical changes can affect the proliferation and protein expression of chondrocytes. Here we investigated the effect of extracellular matrix stiffness on mouse articular chondrocyte phenotype, growth, and subcellular p53 localization. Chondrocytes were seeded on collagen‐coated substrates varying in elasticity: 0.5 and 100 kPa. Immunocytochemical staining and immunoblotting showed that a softer substrate significantly increased p53 nuclear localization in chondrocytes. Furthermore, we identified microRNA‐532 (miR‐532) as a potential p53 target gene to influence cell function, indicating a new target for tissue engineering. These findings provide insight into the influence of physical cues on cell phenotype maintenance and could help improve understanding of cartilage‐related pathologies such as osteoarthritis.